Implementasi Keterampilan Pengelolaan Kelas Guru Pendidikan Agama Islam Di SDN 54/VI Lubuk Birah Jambi - Amelia Putri; Junaidi Junaidi; Arman Husni; Fauzan Fauzan (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2023)
Classroom management is a very important teacher competency to be managed in the context of learning. Therefore, every teacher must have the ability to manage the class. The purpose of this study was to identify the strategies and constraints of Islamic religious education teachers in implementing classroom management skills at SDN 54/VI Lubuk Birah Jambi. This research is field research, the purpose of which is to describe accurately the factual description of the phenomenon under study. In this study there were two informants, namely key informants, Islamic religious education teachers, and supporting informants students and school principals. The results of the study conducted at SDN 54/VI Lubuk Birah Jambi show that teachers use their classroom management skills to implement various strategies, namely:Structuring the learning environment, making lesson plans (RPP), how to teach teachers, building student cooperation, creating a learning atmosphere, shaping behavior and motivating students, evaluating learning. The following barriers were observed in the implementation of classroom management skills: student factors, teacher factors, and facility factors. Student factors, teacher factors and room factors.